Faktor Fundamental Ekonomi Makro terhadap Indeks Harga Saham Properti - Zulkarnain, Ronny Wijaya (Universitas Brawijaya, Indonesia, 2016)
The property sector is very important in the economy of a country. Superpower country like The United States ofAmerica almost dragged into a recession due to a mistake in predicting the property sector. The impact will affect all parts of society, including government, investors and even to ordinary people. Based on that argument, the researcher attempted to analyze the influence of macroeconomic factors on the property sector, especially in the composite stock price index in the property sector. In this study, the author used inflation, exchange rates of Rupiah against the U.S. dollar, Gross Domestic Product (GDP) and the property stock price index in the previous month as the independent variables. Thisstudy used ordinary least square method. The results showed that the combination of the factors is significantly affected the stock price index property sector. On the other hand, some inflation rate and exchange rate have a significant negative impact on property sector index. Meanwhile, the previous month index of the property sector has a significantly positive effect on this month stock price index of the property sector partially. The study also reveals that GDP growth partially did not significantly affectthe stock price index of property sector.